AN ANALYSIS OF STUDENTS’ SKRIPSI ERRORS IN USING ARTICLES AT ENGLISH EDUCATION STUDY PROGRAM OF IKIP GUNUNGSITOLI YEAR 2018/2019 - Telaumbanua, Yasminar Amaerita (Jurnal Review Pendidikan dan Pengajaran, 2020)
Writing skripsi is an obligatory scientific work for students at the last semester at English education study program of IKIP Gunungsitoli. It is done through a research. The research is conducted based on a certain research design. Teacher-researcher did a research to describe what article errors done by the students, how many times the students are writing article errors and why the students cannot revise the article errors successfully particularly in Chapter I. The data source was from the three skripsi done by three students who graduated faster, 3 years and half. As the research findings, the teacher-researcher found there were three kinds of article errors done by the three students in their skripsi in Chapter I namely indefinite article (a, an), definite article (the) and zero article. It’s concluded that the article errors which were done by the three students who wrote their skripsi are indefinite articles (a, an), definite article (the) and zero article, the three students write article errors as 34 times of 27 sentences and the three students cannot revise the article errors successfully because lack of knowledge of using articles as well as lack of attention to find out proof readers to make better papers.